(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this study was to assess the effects of anesthetic drugs on heart rate (HR) and heart rate variability (HRV) in dogs. Materials and Methods: Twelve healthy client-owned dogs of various breeds, including five females and seven males were used for elective surgery in this study. The dogs were pre-medicated with four protocols; (1) alfaxalone [at 3 mg/kg body weight (bwt)], (2) zolazepam + tiletamine (Zoletil) (at 5 mg/kg bwt), (3) diazepam (at 0.3 mg/kg bwt) + ketamine (at 5 mg/kg bwt), and (4) diazepam (at 0.3 mg/kg bwt) + propofol (at 5 mg/kg bwt). The HR and HRV of 12 dogs were recorded 20 min before and after the administration of the anesthetic drugs. Doppler was used to obtain systolic, diastolic, and mean blood pressures. Results: After anesthetic drug administration, the dogs pre-medicated and inducted with alfaxalone had the lowest HR values as compared with those of other protocols. The HRV low frequency and high frequency power ratio decreased in the dogs pre-medicated and intubated with alfaxalone. Conclusion: This study demonstrates that alfaxalone preserves the cardiovascular function; and hence, is considered as safe to use for the surgical applicability in dogs. http://doi.org/10.5455/javar.2018.e303